Performance test of air input control system for paddy grain drying using in-store dryer. Issue 1 (November 2021) - Nurba, D; Agustina, R; Yasar, M; Khurjannah, A
Abstract: The control system is e series of a system that is very important in today's technology. Wherewith control system can make the human job easy and get a good result. This study used a controlled In-Store Dryer to dry 100 kg of grain with an initial moisture content of 17, 77% to reach 14%. The study results using a control system, the average ambient temperature of the three tests ranged from 32°C to 33°C, and the RH ranged from 64, 8 % to 68, 6%. At the same time, the average temperature was 36, 7°C to 37, 5°C, and the average RH was 49, 9% up to 64, 7%. The drying airflow speed at the fan input is 6, 2 m/s and at the chimney 9, 2 m/s. Moisture content during drying differs for each thickness depending on the location, with an average drying rate of 0, 92%. During drying, the moisture content varied for each consistency depending on the site, with the drying rate at an average ISD of 0.92% w / hr. total electrical energy consumption of 32.57 kWh and energy in biomass combustion 1, 416, 600 kJ. The quality during rice drying starts from the initial moisture content of 17.78% to reach the final moisture content of 10.44%.